1993
DOI: 10.1063/1.110539
|View full text |Cite
|
Sign up to set email alerts
|

True oxide electron beam induced current for low-voltage imaging of local defects in very thin silicon dioxide films

Abstract: A new low-voltage contrast mechanism due to electron hole pairs generated in the oxide by an electron beam was observed at an electric field lower than 3.5 MV/cm in addition to the tunneling current microscopy (TCM) contrast mechanism at electric fields higher than 3.5 MV/cm. The new contrast mechanism is opposite in sign to the TCM contrast mechanism. Good contrast can be obtained at an electric field as low as 2.4 MV/cm, which is two to three times smaller than that needed for TCM contrast. Potential applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…8 and 9 and FN expression [I / V 2 expðÀb=VÞ] given in ref. 10. Considering the relationship between EBIC and bias, we have found that the conduction of the EBIC at the background can be fitted well as in TAT (0 to À1:2 V), TAT+DT (À1:2 to À1:5 V), and FN (more than À1:5 V).…”
Section: G Dependencementioning
confidence: 72%
“…8 and 9 and FN expression [I / V 2 expðÀb=VÞ] given in ref. 10. Considering the relationship between EBIC and bias, we have found that the conduction of the EBIC at the background can be fitted well as in TAT (0 to À1:2 V), TAT+DT (À1:2 to À1:5 V), and FN (more than À1:5 V).…”
Section: G Dependencementioning
confidence: 72%
“…A thickness were deposited on SiO 2 / Si [20][21][22][23][24] at 630 C in a mixture of TiCl 4 , NH 3 , and N 2 gases at a stable chamber pressure of 20 mTorr by varying N 2 gas flow rate. We deposited the dielectric materials, i.e., HfO 2 films of 50…”
Section: Tin Thin Films Of 300mentioning
confidence: 99%